Effects of Heme Site (FA1) Ligands Bilirubin, Biliverdin, Hemin, and Methyl Orange on the Albumin Binding of Site I Marker Warfarin: Complex Allosteric Interactions - Lemli, Beáta; Lomozová, Zuzana; Huber, Tamás; Lukács, András; Poór, Miklós (International journal of molecular sciences, 2022)
Human serum albumin (HSA) is the most abundant plasma protein in circulation. The three most important drug-binding sites on HSA are Sudlow's Site I (subdomain IIA), Sudlow's Site II (subdomain IIIA), and Heme site (subdomain IB). Heme site and Site I are allosterically coupled; therefore, their ligands may be able to allosterically modulate the binding affinity of each other. In this study, the effects of four Heme site ligands (bilirubin, biliverdin, hemin, and methyl orange) on the interaction of the Site I ligand warfarin with HSA were tested, employing fluorescence spectroscopic, ultrafiltration, and ultracentrifugation studies. Our major results/conclusions are the following. (1) Quenching studies indicated no relevant interaction, while the other fluorescent model used suggested that each Heme site ligand strongly decreases the albumin binding of warfarin. (2) Ultrafiltration and ultracentrifugation studies demonstrated the complex modulation of warfarin-HSA interaction by the different Heme site markers; for example, bilirubin strongly decreased while methyl orange considerably increased the bound fraction of warfarin. (3) Fluorescence spectroscopic studies showed misleading results in these diligand-albumin interactions. (4) Different Heme site ligands can increase or decrease the albumin binding of warfarin and the outcome can even be concentration dependent (e.g., biliverdin and hemin).
Keywords: Hemin; ligandy; Warfarin; heme site; warfarin; hemin; sérový albumin; hem; Serum Albumin; Ligands; Sudlow’s site I; Humans; Bilirubin; biliverdin; bilirubin; allosteric modulation; Biliverdine; human serum albumin; Heme; lidé